STRATEGIC FORESIGHT AND POLICY AGILITY: NAVIGATING COMPLEXITY AND UNCERTAINTY IN THE ERA OF POLY-CRISIS - Oloda Oluwatayo Felix (American Journals Publishing, 2025)
The acceleration of global poly-crisis, including pandemics and climate shocks, geopolitical volatility and technological disruption, has demonstrated that time-consuming, traditional strategic planning and fixed, hierarchical governance structures do not scale. This theoretical article presents the argument that sustainable advantage and resilience in such turbulent environments requires the merger of two capacities that tend to be separated: strategic foresight and policy agility. With reference to theories of dynamic capabilities, complex adaptive systems and anticipatory governance, we formulate the Foresight-Agility Nexus Model, a model demonstrating how real-time policy implementation can be combined with long-term anticipation of possible futures. Some of the mechanisms that can be highlighted through the model include feedback loops, learning process and foresight-based action that can help organizations and government anticipate and adapt towards uncertainty. By connecting foresight and agility, we propose that decision-makers can also drive innovation, legitimacy, and resilience, thus being able to avoid short-termism and paralysis associated with volatility. The paper makes contributions to the field of strategic management and policy in that it presents an integrative framework that reconstitutes the future as not a horizon to be predicted into a future as an unfolding landscape to be continuously engaged. The consequence of the findings is the recommendation to scholars, policymakers, as well as to business strategists to develop their foresight capabilities, institutionalize their ways of agile governance, and build their hybrid strategies that can be more focused on exploration or exploitation in specific cases. Future research sites are suggested to empirically examine and develop the nexus model within other policy areas and the various organisational settings.